2011
DOI: 10.1159/000332757
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Subclinical Hypothyroidism in Patients with End-Stage Renal Disease and the Role of Serum Albumin: A Cross-Sectional Study from South India

Abstract: Background/Aim: Subclinical hypothyroidism (SCH) and end-stage renal disease (ESRD) are independent risk factors for cardiovascular mortality. We aimed to study the prevalence of SCH in ESRD patients and assessed its associated risk factors. Methods: This cross-sectional study was conducted at 2 tertiary-care centers in Chennai, India, over a 3-year period. The study group comprised 137 patients with ESRD on thrice weekly regular maintenance hemodialysis. Free thyroxine (FT4) and thyroid-stimulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
20
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
9
20
2
Order By: Relevance
“…A similar study was conducted by Shantha et al, where they found the prevalence of SCH was 24.8%. 6 The present study showed that the prevalence of SCH was 25%, which was more in females (52%) as compared to males (48%). This is in contrast to the study of Shantha et al, which showed prevalence of disease was higher in males (73.5%) as compared to females (26.5%) out of 137 ESRD patients.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…A similar study was conducted by Shantha et al, where they found the prevalence of SCH was 24.8%. 6 The present study showed that the prevalence of SCH was 25%, which was more in females (52%) as compared to males (48%). This is in contrast to the study of Shantha et al, which showed prevalence of disease was higher in males (73.5%) as compared to females (26.5%) out of 137 ESRD patients.…”
Section: Discussionsupporting
confidence: 46%
“…This is in contrast to the study of Shantha et al, which showed prevalence of disease was higher in males (73.5%) as compared to females (26.5%) out of 137 ESRD patients. 6 This study has shown a decreased level of serum albumin to be a risk factor for SCH in ESRD patients. Our patients with SCH had significantly lower serum albumin levels compared to patients with normal TSH.…”
Section: Discussionmentioning
confidence: 74%
“…8 In a study by Santha GPS et al reported the prevalence of SCH in ESRD to be 24.8% in Indian Population with a study size of 137 patients with ESRD. 2 In a study by Lim VS the prevalence of SCH in ESRD was 0-9.5%.…”
Section: Introductionmentioning
confidence: 97%
“…1 For ESRD, the estimated prevalence in India is 200 million per inhabitant. 2 Thyroid hormones (TH) have an important role in regulating metabolism, development of the kidney, maintenance of water and electrolyte homeostasis, protein synthesis and influencing other hormone function. Tri-iodothyronine (T3) and Thyroxin (T4) are the two main hormones produced by the thyroid.…”
Section: Introductionmentioning
confidence: 99%
“…isorders of thyroid function are an exceedingly common endocrine complication in patients with chronic kidney disease, including those receiving dialysis (1)(2)(3)(4)(5)(6)(7). Data from the Third National Health and Nutrition Examination Survey have shown an increasing burden of hypothyroidism with incrementally impaired kidney function, such that participants with an estimated glomerular filtration rate (eGFR) of ,45 mL/min/1.73 m had a nearly fivefold higher prevalence compared with those with an eGFR $90 mL/min/1.73 m 2 (;23% vs ;5%, respectively) (2).…”
mentioning
confidence: 99%